Assistive technology: Understanding the needs and experiences of individuals with autism spectrum disorder and/or intellectual disability in Ireland and the UK. Issue 5 (2nd September 2020) - O'Neill, Sean J.; Smyth, Sinéad; Smeaton, Alan; O'Connor, Noel E.
ABSTRACT: Assistive technologies (ATs) aimed at improving the life quality of persons with Autism Spectrum Disorder and/or Intellectual Disability (ASD/ID) is an important research area. Few have examined how this population use and experience AT or their vision for future uses of AT. The present study aimed to update and extend previous research and provides insight from caregivers, and other stakeholders ( n  = 96), living in Ireland and the United Kingdom, on their experiences of assistive technology (AT) for ASD/ID. Caregiver and professional responses to an anonymous online survey showed that focus individuals were rated low in terms of independent and self-management skills, with scheduling and planning and communication identified as desirable future AT functions. Overall, positive experiences of AT were reported, with AT use more than doubling in recent years.